Microwave-Assisted Pyrolysis of Oil Palm Biomass: Multi-Optimisation of Solid Char Yield and Its Calorific Value Using Response Surface Methodology - Idris, Siti Shawalliah; Rahman, Norazah Abd; Ismail, Khudzir; Mohammed Yunus, Mohammed Faisal; Mohd Hakimi, Noor Irma Nazashida (Frontiers in Chemical Engineering, 2022)
Recovery of oil palm resources is essential towards conserving environment. This study investigated the behaviour of oil palm kernel shells (PKS), palm mesocarp fibre (PMF) and empty fruit bunch (EFB) through microwave assisted pyrolysis. Power level (300–1,000 W), exposure time (10–30 min) and mass loading (20–50 g) were varied to determine its influence on char yield and calorific value at one-factor-at-a-time (OFAT) analysis. Model equations obtained from Box-Behnken design was used for Response Surface Methodology (RSM) in determining the optimum operating condition. It was found that the power level has least important influence on the solid char yield of EFB and PMF. No significant impact on the solid char yield of PMF beyond 10 min of exposure. Maximum mass inside the pyrolyser for EFB, PMF, and PKS are 40, 50, and 25 g, respectively. Calorific values of solid char produced were comparable to a low rank coal (>22 MJ/kg). From the RSM analysis, the optimum conditions for obtaining high char yield and calorific values have been determined with power level of 300 W, exposure time in the range of 16.7–32 min, and biomass mass in the range of 20–40.4 g. The outcome from this analysis is vital as it provides an alternative solution to utilise oil palm industrial wastes to be converted to solid fuel as source of renewable fuel and reduce its pollution to the environment.